New ICA criteria for the diagnosis of acute kidney injury in cirrhotic patients: can we use an imputed value of serum creatinine?. (7th May 2015) - Rosi, Silvia; Piano, Salvatore; Frigo, Anna C.; Morando, Filippo; Fasolato, Silvano; Cavallin, Marta; Gola, Elisabetta; Romano, Antonietta; Montagnese, Sara; Sticca, Antonietta; Gatta, Angelo; Angeli, Paolo
Abstract Background & Aims The new International Club of Ascites diagnostic criteria to diagnose acute kidney injury at hospital admission suggests the possibility of using a presumed baseline serum creatinine, defined as the last of at least two stable creatinine values during the last 3 months. Nevertheless, the possibility of the lack of such a value still remains. In these patients, the KDIGO criteria suggest to use an inverse application of MDRD equation assuming that baseline glomerular filtration rate is 75 ml/min per 1.73 m2 (imputed baseline creatinine). We tested the accuracy of this approach to detect acute kidney injury at admission in patients with decompensated cirrhosis and creatinine <1.5 mg/dl. Methods We analysed 213 patients hospitalized for acute decompensation of cirrhosis. At admission, glomerular filtration rate was estimated using creatinine‐based equations and measured by inulin clearance. A diagnosis of acute kidney injury was made using an imputed value of serum creatinine as baseline. Results The diagnosis of AKI based on an imputed baseline creatinine identified only 20.1% of patients with measured glomerular filtration rate ≤60 ml/min/1.73 m2 without any predictive value on 90‐day survival. Conclusions In patients with cirrhosis and ascites with a creatinine <1.5 mg/dl without a baseline value on their records, the diagnosis of acute kidney injury at admission based on an imputed baseline creatinine is not accurate.